2008
DOI: 10.1105/tpc.108.060327
|View full text |Cite
|
Sign up to set email alerts
|

RNase-Based Self-Incompatibility: Puzzled byPollen S 

Abstract: Many plants have a genetically determined self-incompatibility system in which the rejection of self pollen grains is controlled by alleles of an S locus. A common feature of these S loci is that separate pollen-and style-expressed genes (pollen S and style S, respectively) determine S allele identity. The long-held view has been that pollen S and style S must be a coevolving gene pair in order for allelic recognition to be maintained as new S alleles arise. In at least three plant families, the Solanaceae, Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…The RNase activity of S-RNases is essential to the proper functioning of S-RNases in the selfincompatibility response (Huang et al, 1994), but it remains unclear just how the S-RNases can specifically affect the rejection of self-pollen. It has been reported recently that several S-locus F-box proteins control the functions of S-RNases through the ubiquitin/26S proteasome pathway of protein degradation (Qiao et al, 2004;Hua et al, 2007;Newbigin et al, 2008). These reports provide additional support to our hypothesis of the existence of a counterpart protein whose function is to control the regulatory roles of OmBBD in defense responses.…”
Section: Discussionsupporting
confidence: 80%
“…The RNase activity of S-RNases is essential to the proper functioning of S-RNases in the selfincompatibility response (Huang et al, 1994), but it remains unclear just how the S-RNases can specifically affect the rejection of self-pollen. It has been reported recently that several S-locus F-box proteins control the functions of S-RNases through the ubiquitin/26S proteasome pathway of protein degradation (Qiao et al, 2004;Hua et al, 2007;Newbigin et al, 2008). These reports provide additional support to our hypothesis of the existence of a counterpart protein whose function is to control the regulatory roles of OmBBD in defense responses.…”
Section: Discussionsupporting
confidence: 80%
“…It is not obvious how SLFs and S-RNases came to constitute a genetic unit at a single S-locus during evolution of the S-RNase-based-SI system considering the much lower diversity among SLFs relative to S-RNases 11 . We conducted phylogenetic analysis of SLFs and S-RNases including those of other genera of Solanaceae by first exploring SLF-orthologs in the whole-genome databases of tomato (Solanum lycopersicum) and potato (Solanum tuberosum) 12,13 .…”
Section: Solanum S-loci Contain Orthologous Slf-like Paralogsmentioning
confidence: 99%
“…The model predicts that both S 17 -RNase and S 22 -RNase are the targets of conserved SLF1. We previously tested four conserved SLF1 alleles (S 5 , S 7 , S 9 , S 11 ) and showed that all of them targeted S 17 -RNase 9 . Our new experiment confirmed that S 22 -RNase is also the target of a conserved SLF1, S 7 -SLF1 ( Supplementary Fig.…”
Section: Diversity and Deletion Of Slfs Predict Target S-rnasementioning
confidence: 99%
See 1 more Smart Citation
“…The former is the S-ribonuclease gene (S-RNase) and the latter is a pollen-expressed F-box gene called the S haplotype-specific F-box gene (SFB) in Prunus of the Rosaceae and the S locus F-box gene (SLF) in the Solanaceae and Plantaginaceae (Entani et al, 2003;Lai et al, 2002;Qiao et al, 2004;Sijacic et al, 2004;Ushijima et al, 2003Ushijima et al, , 2004Yamane at al., 2003;Wang et al, 2004). Although the Prunus pollen S was originally referred to by two different terms, SFB and SLF (Entani et al, 2003), we use SFB in this article because it distinguishes the Prunus system from other systems, and recent studies have all used SFB (Newbigin et al, 2008;Sassa et al, 2010;Tao and Iezzoni, 2010). The S locus F-box brothers (SFBBs) have been identified as candidates for the pollen S determinant in the subtribe Pyrinae of the Rosaceae (De Franceschi et al, 2011a, 2011bKakui et al, 2011;Minamikawa et al, 2010;Okada et al, 2008Okada et al, , 2011Sassa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%